Glistening formation in a new hydrophobic acrylic intraocular lens - Yildirim, Timur Mert; Fang, Hui; Schickhardt, Sonja; Wang, Qiang; Merz, Patrick; Auffarth, Gerd U. (BMC ophthalmology, 2020)
BACKGROUND: The formation of fluid-filled microvacuoles, termed glistenings, is a common complication of intraocular lenses (IOLs) made from hydrophobic acrylate. Using our well-established in-vitro laboratory method, we evaluated a new IOL material's resistance to glistening formation. METHODS: An in-vitro stress test for glistening induction was performed on 20 samples of hydrophobic acrylic IOLs: ten of the new Eyecryl ASHFY600 (Biotech Vision Care, Ahmedabad, India) compared with ten samples of AcrySof IQ SN60WF (Alcon, Fort Worth, USA). The number of microvacuoles per square millimetre (MV/mm2) was evaluated in five sections of each IOL. The results for each model were compared and rated on a modified Miyata Scale for grading glistening severity. RESULTS: In all cases, glistening number was higher in the central section of the IOL optic than in the periphery. Mean number of MV/mm2 was highest in the central part of the AcrySof IQ SN60WF, with 41.84 (±27.67) MVs/mm2. The lowest number of glistenings was found in the five sections of the Eyecryl ASHFY600 with 0.52 (±0.24) MVs/mm2. Mean value of the Eyecryl ASHFY600 IOL, using the Miyata Scale, was Zero. CONCLUSION: In this in-vitro laboratory study, the new hydrophobic acrylic IOL showed a high resistance to microvacuole formation. Results from this in-vitro study suggest that glistening numbers will be low in clinical use in the Eyecryl ASHFY600.
Gesehen am 17.06.2020